Problems of strengthening the legality and legal order - Каkimova, M.Sh.; Birmanova, A.I. (Издательство КарГУ, 2015)
This article deals with the role and its features of localization, regulation of regularity and law order in the public relations. Regularity and law order are necessary element of the constitutional state therefore based on regularity and the law; the state can provide unshakable steady level of discipline and turn its legal. And also the problems of improvement of the legislation are considered, its role and place in formation and development of the constitutional state. The problems of regularity and law order always pay attention of scientists and civil servants because the condition of the rights and freedoms of the person is directly connected with questions of definition of a political regime of society.
Keywords: legality; legal order; democracy; legal state (constitutional state); state power; reform; subject